Examining links between soil fertility and various nutrient management regimes on yield and quality of sweet potato (Ipomoea batatas) - Mahanjana, Aviwe (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.